Nel·lo, Oriol i Mele, Renata (eds.) (2016). Cities in the 21st Century - Casellas, Antònia (Documents d'Anàlisi Geogràfica, 2018)
Nel·lo, Oriol i Mele, Renata (eds.) (2016) Cities in the 21st Century Londres i Nova York: Routledge, 309 p. ISBN 978-1-138-11963-2